Ibadah Shalat Dalam Naskah Kapasakina Ma’ana Di Tinjau Dalam Maqashid As Syari’ah - Amiruddin Amiruddin (Institut Agama Islam Negeri (IAIN) Kendari, 2018)
Islamic wealth and cultural heritage in Tanah Buton (Wolio) is a manuscript that is still widely stored in the community, one of which is the Kapasakina Ma'ana (KM) script. This manuscript includes a secret manuscript, only a few people know and understand it. This study is aimed at describing, transliterating, editing text, translating, and revealing content, so that it can be used by the wider community. With philological studies, the reader gets an edition of the text, transliteration, translation, and description of the text and the contents of the text. The method used is the philological method. Sociologically, it can be found that this manuscript is written in Wolio with the script (buri) of Wolio. The contents of the KM manuscript consist of 10 parts, namely (1) the nature of prayer, (2) the nature of Allahu akbar, (3) the position and function of the four elements in prayer, (4) the nature of laa ilaaha illallah, (5) the position of Allah and the Prophet Muhammad , (6) forms and fadilah of dhikr and prayers, (7) some of the fadilah asmaul husna, (8) prayers and aqiqah and qurban, (9) procedures for the prayer, and (10) prerequisites for repentance.